Employees’ Engagement at Work: The Role of Workplace Health and Safety - Raiza Mae Calbonero Narciso; Hilbert S. Narciso (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The main objective of this study was to investigate if there is a correlation between workplace health and safety and employee engagement. Random sampling technique was used in identifying the respondents and sample size of this study. Design/methodology/approach: This study used the quantitative non-experimental research design using correlational technique with mean, pearson-r, and t-test as statistical tools. A validated survey questionnaire was used as principal data collection instrument. Findings: Results revealed that the level of workplace health and safety was very high. Same goes with the level of employee engagement which was also very high. Finally, findings showed that there was a significant relationship between workplace health and safety and employee engagement. Research limitations/implications: The implication of this study to the global setting is that as employee engagement is vital in an academic institution, colleges and universities may provide different intervention programs to employees in order to increase the level of employee engagement in their institution. Since COVID is a Global issue it must also be considered that different programs must be given in accordance with the current practices in this pandemic. Paper type: Research paper